Neurological Characteristics of Pediatric Glycogen Storage Disease - Muzetti, Julio Henrique; do Valle, Daniel Almeida; Santos, Mara L. S. Ferreira; Telles, Bruno Augusto; Cordeiro, Mara L. (Frontiers in Endocrinology, 2021)
Glycogen storage diseases (GSD) encompass a group of rare inherited diseases due dysfunction of glycogen metabolism. Hypoglycemia is the most common primary manifestation of GSD, and disturbances in glucose metabolism can cause neurological damage. The aims of this study were to first investigate the metabolic, genetic, and neurological profiles of children with GSD, and to test the hypothesis whether GSD type I would have greater neurological impact than GSD type IX. A cross-sectional study was conducted with 12 children diagnosed with GSD [Types: Ia (n=5); 1, Ib (n=1); 4, IXa (n=5); and 1, IXb (n=1)]. Genetic testing was conducted for the following genes using multigene panel analysis. The biochemical data and magnetic resonance imaging of the brain presented by the patients were evaluated. The criteria of adequate metabolic control were adopted based on the European Study on Glycogen Storage Disease type I consensus. Pathogenic mutations were identified using multigene panel analyses. The mutations and clinical chronology were related to the disease course and neuroimaging findings. Adequate metabolic control was achieved in 67% of patients (GSD I, 43%; GSD IX, 100%). Fourteen different mutations were detected, and only two co-occurring mutations were observed across families (GSP6 c.247C>T and c.1039C>T). Six previously unreported variants were identified (5 PHKA2; 1 PHKB). The proportion of GSD IX was higher in our cohort compared to other studies. Brain imaging abnormalities were more frequent among patients with GSD I, early-symptom onset, longer hospitalization, and inadequate metabolic control. The frequency of G6PC mutations was similar to that observed among the North American and European populations. None of the mutations observed in PHKA2 have been described previously. Therefore, current study reports six GSD variants previously unknown, and neurological consequences of GSD I . The principal neurological impact of GSD appeared to be related to inadequate metabolic control, especially hypoglycemia.